THE COMPOSITION OF NONIONIC SURFACTANT MIXTURES AT THE AIR/WATER INTERFACE AS DETERMINED BY NEUTRON REFLECTIVITY - Penfold, J; Staples, E; Thompson, L; Tucker, I (1995)
Neutron reflectivity has been used to study the adsorption of non-ionic mixtures at the air/water interface. Measurements have been made over a wide concentration range from below to above the critical micellar concentration (CMC), (10-5-10-2 M). The data provides a direct qualitative confirmation of the abrupt changes in surface composition at the CMC due to the onset of mixed micelle formation predicted recently by Nikas, Puvvada, and Blankschtein, Langmuir, 8 (1992) 2680. The data for concentrations below the CMC are compared with the earlier results of Rosen and Hua, J. Colloid Interface Sci., 86 (1982) 164. © 1996.